Active flow control by means of endwall synthetic jet on a high-speed compressor stator cascade. (September 2018) - Qin, Yong; Song, Yanping; Chen, Fu; Wang, Ruoyu; Liu, Huaping
The underlying physics of the endwall synthetic jet in improving the aerodynamic performance of a high-speed compressor stator cascade is investigated in this paper. The effects of both injected momentum and actuation frequency are discussed in detail. In the investigations, the injected momentum is controlled by either changing the maximum jet velocity or modifying the tube diameter. Numerical results demonstrate that the streamwise momentum addition and flow mixing enhancement are the key factors of the endwall synthetic jet in improving the cascade performance. The high momentum fluid injected into the flow field can reenergize the passage flow, and the generated streamwise jet vortex contributes to the strengthening of flow mixing. Consequently, the momentum exchange between the low momentum fluid region and the main flow is enhanced and boundary layer separation on the blade suction surface is delayed. The loss characteristic in the corner region is improved as well. The intensified flow mixing will also increase the total pressure loss in the near-endwall region, which as a result will worsen the cascade performance, and hence the total effect of the endwall synthetic jet depends on the sum of its impacts. Moreover, the injected momentum and the actuation frequency have strong influences on the flow control effect. With the momentum coefficient and the reduced frequency being Cµ  = 0.131% and F +  = 1.0, the reduction in total pressure loss coefficient and the increment in pressure rise coefficient are 7.3% and 3.3%, respectively.